Extreme wildfire : smoke jumpers, high-tech gear, survival tactics, and the extraordinary science of fire - Thiessen, Mark (Photographer); Phelan, Glen (National Geographic, 2016)
"From a searing expanse of flames in Russia to barreling blazes in California, no wildfire is too extreme for National Geographic photographer and wildland firefighter Mark Thiessen. Travel with Thiessen across the globe as he investigates dangerous infernos and works alongside courageous firefighting teams. Offering stunning photography, expert advice, and inside information on the most high-tech gear, the author turns up the heat to show you the incredible science behind the flames."